The Roanoke girls : a novel - Engel, Amy (New York : Crown Publishers, 2017)
Returning to her family's Kansas estate in the hopes of discovering the fate of her missing cousin, Lane reconnects with a young man from her past and is confronted by dark family secrets that prompted her to flee years earlier.
Keywords: Missing persons -- Fiction; Family secrets -- Fiction; Missing persons -- Fiction; Secrecy -- Fiction; Suspense fiction; Suspense fiction